(3eOGFM TYQjI hfKQjIs - (3LdGd GdOjf Hf NjQ GdOjf GdMfajs
(3ChdgG (B:s
(3hHYO aEfg deG cGf GdCOH CTQa UfGYI gPG, Ke Gfj CgOjJ Edi HGHg GdTQja gPg GdeOGFM s
(3BNQgG (B:s
(3LdGd GdOjf Hf NjQGdOjf GdMfaj, OGYjkG ddeYfi HgPG GdNWGH, hGdegOj Edi LfGHg gPG GdcJGH hGdMeO ddg hMOg s
(3eged GdfbW CMjGfkG s
(3gfGc Tc aj fSHI GdeNWhW ddeDdas
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B48 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs